Increased HLA class II risk is associated with a more aggressive presentation of clinical type 1 diabetes - Kieleväinen Vilma; Turtinen Maaret; Luopajärvi Kristiina; Härkönen Taina; Ilonen Jorma; Knip Mikael; Finnish Pediatric Diabetes Register (John Wiley and Sons Inc, 2025)
Aim: To determine the association of HLA class II risk with the demographic and clinical characteristics of type 1 diabetes at diagnosis.
Methods: We conducted a register-based retrospective cohort study of 4993 Finnish children (2169 girls) - diagnosed with type 1 diabetes under the age of 15 years in 2003-2016. The participants were divided into six risk groups based on their HLA DR/DQ genotype. Demographic characteristics, family history of type 1 diabetes and metabolic markers at the time of diagnosis were compared between the groups.
Results: In total, 4056/4993 children (81.2%) carried an HLA genotype associated with an increased risk of type 1 diabetes (risk groups 3-5), whereas 937/4993 children (18.8%) carried a HLA genotype conferring no or decreased disease risk. Children with higher HLA risk were younger at diagnosis (p < 0.001) and had a shorter duration of classical symptoms before diagnosis (p = 0.016). Subjects in the high-risk group were more likely to have a family member affected by type 1 diabetes when compared to those in the neutral risk group (11.5% vs. 8.8%, p = 0.05).
Conclusion: Children with stronger HLA disease susceptibility are younger at their disease manifestation and have a shorter period of symptoms before diagnosis, suggesting that the HLA class II genes are associated with a more aggressive disease presentation.